A high remanence samarium cobalt permanent magnet material and preparation method thereof

By introducing auxiliary alloys into samarium-cobalt permanent magnet materials and optimizing their microstructure using a multi-step process, the problem of insufficient residual magnetism and coercivity at room temperature is solved, and the comprehensive magnetic performance improvement of high residual magnetism and high coercivity is achieved, which is suitable for applications in high-tech fields.

CN115579205BActive Publication Date: 2025-04-01INNER MONGOLIA RARE EARTH FUNCTIONAL MATERIALS INNOVATION CENT CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211407292.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-10
Publication Date
2025-04-01
Estimated Expiration
2042-11-10

AI Technical Summary

Technical Problem

The existing samarium-cobalt permanent magnet materials have low residual magnetism, coercive force and magnetic energy accumulation at room temperature, and are sensitive to production conditions, making it difficult to increase their residual magnetism and coercive force at the same time.

Method used

By introducing auxiliary alloys, the phase components distribution of magnet cell walls is changed, and the microstructure of samarium-cobalt permanent magnet materials is optimized and its remanent magnetism and coercive force is improved.

Benefits of technology

It has achieved high residual magnetism (greater than 11.8kGs) and high coercive force (greater than 25kOe) of samarium-cobalt permanent magnet material, which has improved its comprehensive magnetic performance and is suitable for high-tech fields such as 5G intelligent and hybrid motors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003937058430000071
    Figure BDA0003937058430000071
  • Figure BDA0003937058430000091
    Figure BDA0003937058430000091
  • Figure BDA0003937058430000101
    Figure BDA0003937058430000101
Patent Text Reader

Abstract

The invention discloses a high remanence samarium cobalt permanent magnet material and a preparation method thereof. The material comprises the steps of double alloy rapid solidification smelting, hydrogen crushing, air flow grinding, pressing orientation molding, sintering, solid solution and aging treatment, and creatively introduces an auxiliary alloy into the samarium cobalt permanent magnet to change the distribution of the magnet cell wall phase components, so as to compensate for the defect that when the Fe content increases, the magnet cell intraphase grows rapidly, the volume fraction increases significantly, and the cell wall phase is partially missing, the phenomenon of poor copper at the grain boundary is improved, the grain boundary regulation is realized, the magnet microstructure is improved, the magnet remanence is increased, and the comprehensive magnetic properties of the product are improved. The preparation process is easy to control, the method is simple, and the remanence of the prepared magnetic material is greater than 11.8 kGs and the coercive force is greater than 25 kOe.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnetic material preparation, and relates to a samarium cobalt permanent magnetic material and a preparation method thereof, and specifically relates to a high remanence samarium cobalt permanent magnetic material and a preparation method thereof. Background Art

[0002] Permanent magnetic materials play an important role in various fields of today's society. They are important functional materials that promote social development and have an irreplaceable role. Before the emergence of NdFeB compounds, SmCo alloys were the main rare earth permanent magnetic materials. Compared with NdFeB, SmCo magnets are relatively expensive. At room temperature, their remanence, coercive force and magnetic energy product are lower than those of sintered NdFeB magnets, and their squareness is poor, which greatly limits the scope of use of SmCo sintered permanent magnetic materials. However, its high temperature (above 200°C) performance is unmatched by NdFeB permanent magnets.

[0003] Since 2021, the price of NdFeB raw materials has remained high. Compared with other types of permanent magnet materials such as NdFeB, SmCo permanent magnet materials, as the second-generation rare earth permanent magnet materials, are widely used in automobiles, transportation, computer technology, radar, satellite communications and aerospace technology due to their excellent comprehensive properties such as high temperature stability, strong corrosion resistance and high energy supply. The development of high remanence SmCo magnets can replace NdFeB magnets within a certain range of use, and can expand the application of SmCo magnets in new high-tech fields such as 5G intelligence and hybrid power. Therefore, it is very necessary to conduct in-depth research and development of SmCo magnets with high remanence and high magnetic energy product.

[0004] At present, the research on improving the remanence of samarium cobalt magnets is mainly focused on the research of magnetic material composition and preparation process. Generally speaking, the higher the coercive force of the magnetic material, the stronger its anti-demagnetization ability, the better the stability, and the higher the operating temperature. However, coercive force and remanence are a pair of mutually restrictive factors. Only high remanence can obtain samarium cobalt permanent magnet materials with larger magnetic energy product, and high remanence can obtain a larger surface magnetic field. Therefore, how to obtain high remanence samarium cobalt magnets under the premise of improving coercive force has become a topic that needs to be studied. In the formula design of samarium cobalt magnets, the remanence performance can be improved by increasing the Fe content, but the increase in Fe content makes the production conditions of samarium cobalt magnets extremely sensitive, and the yield rate decreases. At the same time, increasing the Fe content will cause the intracellular phase of the magnet to grow rapidly, and the volume fraction will increase significantly, resulting in the defect of partial missing of the cell wall phase, which will lead to the insignificant effect of improving the remanence. In addition, the increase in Fe content will reduce the coercive force of the magnet. However, in order to improve the coercivity of the magnet, other non-magnetic phases need to be introduced. However, the introduction of any non-magnetic phase (element) will more or less reduce the remanence of the magnet while improving the coercivity, which will make the preparation of high remanence and high coercivity magnets difficult to achieve.

[0005] Therefore, how to prepare high remanence and high coercivity magnets is of great significance to the development of the samarium cobalt industry. Summary of the invention

[0006] The present invention aims to provide a high remanence samarium cobalt permanent magnet material and a preparation method thereof, comprising the steps of rapid solidification smelting of main and auxiliary alloys, hydrogen crushing, air flow grinding, pressing and orientation molding, sintering, solid solution and aging treatment, and creatively introducing an auxiliary alloy into the samarium cobalt permanent magnet to change the distribution of the components of the magnet cell wall phase, to compensate for the defect that when the Fe content increases, the intracellular phase of the magnet grows rapidly, the volume fraction increases significantly, and the cell wall phase is partially missing, the phenomenon of poor copper at the grain boundary is improved, the grain boundary regulation is realized, the microstructure of the magnet is improved, the remanence of the magnet is increased, and the comprehensive magnetic properties of the product are improved. The remanence of the prepared magnetic material is greater than 11.8 kGs, and the coercive force is greater than 25 kOe.

[0007] The technical solution of the present invention is as follows:

[0008] A high remanence samarium cobalt permanent magnet material, the composition is expressed by weight percentage as Sm u (Pr 20 Nd 80 ) w Co a Cu b Zr c Ti d Fe f , wherein: u = 24 ~ 27wt%, w = 3 ~ 7.5wt%, a = 31.5 ~ 48wt%, b = 3.28 ~ 8.2wt%, c = 1.92 ~ 4.5wt%, d = 0.6 ~ 1.5wt%, and f = remainder.

[0009] The present invention also provides a method for preparing a high remanence samarium cobalt permanent magnet material, which is carried out in the following steps in sequence:

[0010] S1. Preparation of the first and second castings

[0011] The first casting sheet and the second casting sheet are prepared by a rapid solidification smelting method, wherein the chemical composition of the first casting sheet is expressed as Sm in weight percentage. g Co h Cu i Zr j Fe 1-h-i-j , wherein g = 25-30wt%, h = 35-50wt%, i = 3-8wt%, j = 2-5wt%; the second casting composition is expressed in weight percentage as (Pr 20 Nd 80 ) 75 Ti 15 Cu 10 ;

[0012] S2, coarse crushing

[0013] The first casting sheet and the second casting sheet are hydrogen crushed, and the addition amount of the second casting sheet is controlled to account for 4-10% of the total weight of the two casting sheets, and the coarse powder of samarium-cobalt dual alloy with a particle size of 10-150 μm is obtained through coarse crushing;

[0014] The addition amount of the two castings is critical, which affects the organizational composition and distribution of the final permanent magnet, and further affects the remanence and coercivity of the permanent magnet. When the content of the first casting is too high, it will cause the cellular structure to grow and the defects of the cell wall phase to increase, making the coercivity of the permanent magnet abnormally low. When the content of the second casting is too high, a large amount of non-magnetic phase will enter the cellular structure, making the remanence of the permanent magnet low.

[0015] S3, air flow milling

[0016] The samarium-cobalt dual alloy coarse powder is added with an antioxidant, and the powder is ground by a jet mill at a grinding pressure of 0.5-0.6 MPa for 30-60 minutes to obtain a fine powder with a D50 of 4-6 μm, and a lubricant is added to the fine powder and stirred for 1.5-4 hours to obtain a uniform samarium-cobalt dual alloy fine powder;

[0017] S4, Orientation Molding

[0018] The fine powder of samarium-cobalt dual alloy is pressed and oriented to form a magnet with a density of 5.2-5.8 g / cm 3 ;

[0019] S5, cold isostatic pressing

[0020] The magnet is wrapped in a plastic bag, evacuated, and then cold isostatically pressed in an isostatic pressing device to obtain a density of 6.1 to 6.8 g / cm 3 of green body;

[0021] S6. Sintering and solution treatment

[0022] The green body is sintered at 1200-1250°C for 1-3 hours, then cooled to 1150-1190°C for 3-6 hours for solution treatment, and then rapidly cooled to room temperature by air;

[0023] S7, aging treatment

[0024] The product in step S6 is subjected to aging treatment to obtain a high remanence samarium cobalt permanent magnet material.

[0025] As a limitation of the preparation method of the present invention:

[0026] (i) In step S1, the casting temperatures of the first casting sheet and the second casting sheet are 1350-1450° C., and the thicknesses are 0.1-0.5 mm, respectively.

[0027] (ii) In step S3, the antioxidant is an ester, and the addition amount thereof is 0.5‰ to 1‰ of the weight of the samarium-cobalt dual alloy coarse powder; the lubricant is an alkane, and the addition amount thereof is 0.1‰ to 1.5‰ of the weight of the fine powder.

[0028] (iii) In step S4, the orientation magnetic field is 1.8 to 2.2 T, and the molding pressure is 3 to 5 MPa.

[0029] (iv) In step S5, the cold isostatic pressing pressure is 180-220 MPa, and the holding time is 10-30 s.

[0030] (V) In step S7, the aging treatment is a primary aging treatment and a secondary aging treatment in sequence, wherein the primary aging treatment is kept at 860°C for 9 hours, then cooled for the first time and the secondary aging treatment is carried out, and the secondary aging treatment is kept at 420°C for 6 hours, then cooled for the second time to 20-30°C.

[0031] The aging treatment is mainly to transform the organizational structure and component phase of the sintered green body, and the aging treatment process affects the level of its coercive force, etc.; the present invention adopts a two-stage aging treatment process to treat the magnet, and the migration of cell wall phase, lamellar phase and the like can occur through the first-stage aging treatment. In this step, the temperature and holding time of the aging treatment are crucial to the migration of phases in the magnet. Within this temperature range, the cell wall phase increases and the lamellar phase is generated. Through the second-stage aging treatment, crystal phase changes such as cell wall phase, lamellar phase and impure phase can occur. In this step, the temperature and holding time of the aging treatment are crucial to the crystal phase changes. Within this temperature range, the composition and structure of the cell wall phase and the lamellar phase are further optimized, and the impure phase is eliminated.

[0032] As a further limitation of the preparation method of the present invention:

[0033] (i) In step S1, the proportion of the first castings with a thickness of 0.2 to 0.35 mm accounts for ≥ 80% of the total; the proportion of the second castings with a thickness of 0.2 to 0.35 mm accounts for ≥ 80% of the total.

[0034] The thickness of the first casting sheet and the second casting sheet in the present invention affects the uniformity of the components, the crystal structure and quantity of the cellular organization of the samarium cobalt permanent magnet, and further affects the residual magnetism and coercive force of the final permanent magnet.

[0035] (ii) In step S7, the cooling rate of the first cooling is 0.15-0.8°C / min, and the cooling method of the second cooling is argon gas air cooling.

[0036] During the cooling process, changes such as phase precipitation and atomic diffusion occur. During the first cooling, atoms such as copper and titanium gradually and evenly migrate and gather in the cell wall phase and repair boundary defects, and elements such as praseodymium and neodymium diffuse into the intracellular phase. The cooling rate at this time affects the amount of copper and titanium migration and the distribution of the cell wall phase structure and composition, whether the cell wall phase has defects, and the distribution of praseodymium and neodymium in the intracellular phase. During the second cooling, defects such as the cell wall phase are further reduced, the rare earth titanium compound phase is more solidified, and the non-magnetic impurity phase is reduced. The purpose of air cooling at this time is to quickly solidify the cell wall phase, rare earth titanium compound and other organizational structures, reduce impurity phases, and improve the magnetic properties of the magnet.

[0037] The present invention also has a limitation that the remanence of the high remanence samarium cobalt permanent magnet material is greater than 11.8 kGs and the coercive force is greater than 25 kOe.

[0038] The present invention mainly adopts dual alloy process, introducing (Pr 20 Nd 80 ) 75 Ti 15 Cu 10 Alloy, alloy (Pr 20 Nd 80 ) replaces the Sm element in the samarium cobalt magnet to further improve the remanence of the magnet, and at the same time the coercive force is also increased to a certain extent; the addition of Cu element in the alloy can generate more Sm (Co, Cu) after secondary aging treatment 5 Phase, can make up for the defect of partial missing of cell wall phase when Fe content increases, while making the intracellular phase of magnet grow rapidly and the volume fraction increase greatly, and optimize the continuous distribution of copper content of cell wall phase, improve the phenomenon of poor copper at grain boundary; the rare earth titanium compound formed by the addition of Ti element is a high melting point alloy, which constructs a part of fine crystallization area in the crystal cell, inhibits the impurity phase generated after the high Fe magnet is solid-solution, thereby obtaining a uniform cellular organizational structure and improving the magnetic energy product of samarium cobalt magnet. The present invention realizes grain boundary regulation, improves the microstructure of magnet, and improves the remanence of magnet by optimizing component design, so as to obtain a high-performance samarium cobalt permanent magnet with remanence greater than 11.8kGs and coercive force greater than 25kOe.

[0039] The preparation method of the present invention is a complete whole, and the various steps are closely related and inseparable, and jointly determine and influence the performance of the product samarium cobalt permanent magnet.

[0040] The beneficial effects achieved by the present invention after adopting the above technical solution are as follows:

[0041] The invention overcomes the problems of poor orientation and low saturation magnetization intensity of traditional samarium cobalt magnets by rationally designing the components of the samarium cobalt permanent magnet material and adopting a dual alloy process. The invention realizes grain boundary regulation and improves the microstructure of the magnet through the synergistic effect of various elements between the raw materials. The remanence of the magnet is increased while the coercive force is increased. The obtained samarium cobalt permanent magnet material has a structure of a 2:17 type samarium cobalt rhombohedral cell structure with a high iron content containing praseodymium, neodymium and titanium, the remanence of the magnet is greater than 11.8 kGs, and the coercive force is greater than 25 kOe.

[0042] The present invention is suitable for preparing high remanence samarium cobalt permanent magnet materials, and is further applied to 5G intelligent and hybrid motors. DETAILED DESCRIPTION

[0043] In the following examples, the reagents described are all commercially available unless otherwise specified, and the following experimental methods and detection methods are all based on existing experimental methods and detection methods unless otherwise specified.

[0044] Example 1 A method for preparing a high remanence samarium cobalt permanent magnet material

[0045] This embodiment is a method for preparing a high remanence samarium cobalt permanent magnet material, which is carried out in the following steps in sequence:

[0046] S1. Preparation of the first and second castings

[0047] The first casting sheet and the second casting sheet are prepared by a rapid solidification smelting method (rapid solidification sheet throwing process) and casting, and the chemical composition of the first casting sheet is Sm in weight percentage. 27 Co 40 Cu 5 Zr 3 Fe 25 The second casting composition is as follows by weight percentage (Pr 20 Nd 80 ) 75 Ti 15 Cu 10 Alloy; the first casting process is a casting temperature of 1430°C to obtain a first casting with a thickness of 0.1 to 0.5 mm (of which the number of castings with a thickness of 0.2 mm to 0.35 mm accounts for ≥80%); the second casting process controls the casting temperature at 1420°C to obtain a second casting with a thickness of 0.1 to 0.5 mm (of which the number of castings with a thickness of 0.2 mm to 0.35 mm accounts for ≥80%);

[0048] S2, coarse crushing

[0049] The first casting sheet and the second casting sheet are hydrogen crushed, and the addition amount of the second casting sheet is controlled to account for 7% of the total weight of the two casting sheets, and the coarse powder of samarium-cobalt dual alloy with a particle size of 10-150 μm is obtained through coarse crushing;

[0050] S3, air flow milling

[0051] The coarse powder of samarium-cobalt dual alloy is added with zinc stearate in an amount of 0.8‰ of the weight of the coarse powder of samarium-cobalt dual alloy, and the powder is ground by jet mill at a grinding pressure of 0.6MPa for 60min to obtain fine powder with a D50 of 4-6μm, and 120# aviation gasoline is added to the fine powder in an amount of 1‰ of the weight of the fine powder, and the powder is stirred for 3h to obtain uniform fine powder of samarium-cobalt dual alloy;

[0052] S4, Orientation Molding

[0053] Take the Sm-Co alloy fine powder and press it under the orientation magnetic field of 2T and the molding pressure of 4MPa to form the magnet with a density of 5.2g / cm 3 ;

[0054] S5, cold isostatic pressing

[0055] The magnet was wrapped in a plastic bag, evacuated, and then cold isostatically pressed in an isostatic pressing device at a pressure of 200 MPa and maintained for 20 seconds to obtain a density of 6.5 g / cm 3 of greenware;

[0056] S6. Sintering and solution treatment

[0057] The green body was sintered at 1210°C for 1.5 hours, then cooled to 1160°C for 5 hours for solution treatment, and rapidly cooled to room temperature.

[0058] S7, aging treatment

[0059] The product in step S6 is subjected to primary aging treatment and secondary aging treatment in sequence, wherein the primary aging treatment is kept at 860°C for 9 hours, cooled at a cooling rate of 0.35°C / min, and then cooled to 420°C for 6 hours for the secondary aging treatment, and then cooled to 20-30°C with argon air to obtain samarium cobalt permanent magnet material. The chemical composition of the material is expressed as Sm in weight percentage. 25.11 (Pr 20 Nd 80 ) 5.25 Co 37. 2 Cu 5.35 Zr 2.79 Ti 1.05 Fe 23.25 .

[0060] The magnet prepared in this embodiment is tested by a BH tester (or a pulse magnetometer), and the remanence of the magnet is 11.91 kGs and the coercive force is 25.42 kOe.

[0061] Example 2-4 Preparation method of high remanence samarium cobalt permanent magnet material

[0062] The present embodiments are respectively methods for preparing a high remanence samarium cobalt permanent magnet material. The preparation process is similar to that of Embodiment 1, and the only difference is that the corresponding technical parameters in the preparation process are different.

[0063]

[0064] Example 5-8 Preparation method of high remanence samarium cobalt permanent magnet material

[0065] In this embodiment, a high remanence samarium cobalt permanent magnet material is prepared respectively. The preparation method is the same as that in Example 1, except that the chemical composition of the first casting sheet and the finally prepared samarium cobalt permanent magnet material in the preparation process is different, as follows:

[0066] Comparative Example

[0067] In the preparation process of samarium cobalt permanent magnet materials, different alloy formulas directly affect the performance of the final prepared product. In order to explore it, the following experiments were carried out:

[0068] Comparative Example 1

[0069] 1) The ingredients are prepared according to the formula design. The first casting composition is Sm in weight percentage. 20 Co 40 Cu 5 Zr 3 Fe 32 The second casting composition is (Pr 20 Nd 80 ) 75 Ti 15 Cu 10 alloy.

[0070] 2) This group of examples prepares a samarium cobalt permanent magnet. The preparation method of Comparative Example 1 is similar to that of Example 1, except that the composition of the casting alloy in step S1 is different, as shown in 1) of Comparative Example 1. The magnetic properties of the prepared product at 20°C are tested using a BH tester (or a pulse magnetometer), as shown in Table 2.

[0071] Comparative Example 2

[0072] 1) The ingredients are prepared according to the formula design. The first casting composition is Sm in weight percentage. 35 Co 40 Cu 5 Zr 3 Fe 17 The second casting composition is (Pr 20 Nd 80 ) 75 Ti 15 Cu10 alloy.

[0073] 2) This group of examples prepares a samarium cobalt permanent magnet. The preparation method of Comparative Example 2 is similar to that of Example 1, except that the composition of the casting alloy in step S1 is different, as shown in 1) of Comparative Example 2. The magnetic properties of the prepared product at 20°C are tested using a BH tester (or a pulse magnetometer), as shown in Table 2.

[0074] Comparative Example 3

[0075] 1) The ingredients are prepared according to the formula design. The first casting composition is Sm in weight percentage. 24 Co 55 Cu 5 Zr 3 Fe 13 The second casting composition is (Pr 20 Nd 80 ) 75 Ti 15 Cu 10 alloy.

[0076] 2) This group of examples prepares a samarium cobalt permanent magnet. The preparation method of Comparative Example 3 is similar to that of Example 1, except that the composition of the casting alloy in step S1 is different, as shown in 1) of Comparative Example 3. The magnetic properties of the prepared magnet at 20°C are tested with a BH tester (or a pulse magnetometer), as shown in Table 2.

[0077] Comparative Example 4

[0078] 1) The ingredients are prepared according to the formula design. The first casting composition is Sm in weight percentage. 27 Co 40 Cu 5 Zr 3 Fe 25 The second casting composition is Gd in weight percentage. 75 Ti 15 Cu 10 alloy.

[0079] 2) This group of examples prepares a samarium cobalt permanent magnet. The preparation method of Comparative Example 4 is similar to that of Example 1, except that the composition of the casting alloy in step S1 is different, as shown in 1) of Comparative Example 4. The magnetic properties of the prepared product at 20°C are tested using a BH tester (or a pulse magnetometer), as shown in Table 2.

[0080] Comparative Example 5

[0081] 1) The ingredients are prepared according to the formula design. The first casting composition is Sm in weight percentage. 27Co 40 Cu 5 Zr 3 Fe 25 The second casting composition is (Pr 20 Nd 80 ) 75 Zr 15 Cu 10 alloy.

[0082] 2) This group of examples prepares a samarium cobalt permanent magnet. The preparation method of comparative example 5 is similar to that of embodiment 1, except that the composition of the casting alloy in step S1 is different, as shown in 1) of comparative example 5. The magnetic properties of the prepared product at 20°C are tested using a BH tester (or a pulse magnetometer), as shown in Table 2.

[0083] Comparative Example 6

[0084] 1) The ingredients are prepared according to the formula design. The first casting composition is Sm in weight percentage. 27 Co 40 Cu 5 Zr 3 Fe 25 The second casting composition is (Pr 20 Nd 80 ) 75 Ti 15 Al 10 alloy.

[0085] 2) This group of examples prepares a samarium cobalt permanent magnet. The preparation method of Comparative Example 6 is similar to that of Example 1, except that the composition of the casting alloy in step S1 is different, as shown in 1) of Comparative Example 6. The magnetic properties of the prepared magnet at 20°C are tested using a BH tester (or a pulse magnetometer), as shown in Table 2.

[0086] Table 2 Properties of samarium cobalt permanent magnets prepared from different alloys at 20°C

[0087]

[0088]

[0089] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of protection of the claims of the present invention.

Claims

1. A high remanence samarium cobalt permanent magnet material, characterized in that: The composition is expressed as Sm in weight percentage. u (Pr 20 Nd 80 ) w Co a Cu b Zr c Ti d Fe f , where: u=24~27wt%, w=3~7.5wt%, a=31.5~48 wt%, b=3.28~8.2 wt%, c=1.92~4.5 wt%, d=0.6~1.5wt%, f=remainder; The method for preparing the high remanence samarium cobalt permanent magnet material is carried out in the following steps in sequence: S1. Preparation of the first and second castings The first casting sheet and the second casting sheet are prepared by rapid solidification smelting and casting, and the chemical composition of the first casting sheet is expressed as Sm in weight percentage. g Co h Cu i Zr j Fe 100-h-i-j-g , wherein g=25~30 wt%, h=35~50 wt%, i=3~8 wt%, j=2~5wt%; the second casting composition is expressed in weight percentage as (Pr 20 Nd 80 ) 75 Ti 15 Cu 10 ; S2, coarse crushing The first casting and the second casting are hydrogen crushed, and the addition amount of the second casting is controlled to account for 4-10% of the total weight of the two castings, and the coarse powder of samarium-cobalt dual alloy with a particle size of 10-150 μm is obtained through coarse crushing; S3, air flow milling The samarium-cobalt dual alloy coarse powder is added with an antioxidant, and the powder is ground by jet milling at a grinding pressure of 0.5-0.6 MPa for 30-60 min to obtain a fine powder with a D50 of 4-6 μm, and a lubricant is added to the fine powder and stirred for 1.5-4 h to obtain a uniform samarium-cobalt dual alloy fine powder; S4, Orientation Molding The fine powder of samarium-cobalt dual alloy is pressed and oriented to form a magnet with a density of 5.2~5.8g / cm³. S5, cold isostatic pressing The magnet was wrapped in a plastic bag, evacuated, and then cold isostatically pressed in an isostatic pressing device to obtain a density of 6.1-6.8 g / cm 3 of green body; S6. Sintering and solution treatment The green body is sintered at 1200-1250℃ for 1-3 hours, then cooled to 1150-1190℃ and kept for 3-6 hours for solution treatment, and then quickly air-cooled to room temperature; S7, aging treatment The product in step S6 is subjected to aging treatment to obtain a high remanence samarium-cobalt permanent magnet material; The aging treatment is a primary aging treatment and a secondary aging treatment in sequence, wherein the primary aging treatment is kept at 860°C for 9 hours, then cooled for the first time and the secondary aging treatment is carried out, and the secondary aging treatment is kept at 420°C for 6 hours, then cooled for the second time to 20-30°C.

2. The high remanence samarium cobalt permanent magnet material according to claim 1, characterized in that: In step S1, the casting temperatures of the first casting sheet and the second casting sheet are 1350-1450° C., and the thicknesses are 0.1-0.5 mm, respectively.

3. The high remanence samarium cobalt permanent magnet material according to claim 2, characterized in that: In step S1, the proportion of the first castings with a thickness of 0.2-0.35 mm accounts for ≥80% of the total amount; the proportion of the second castings with a thickness of 0.2-0.35 mm accounts for ≥80% of the total amount.

4. The high remanence samarium cobalt permanent magnet material according to claim 1, characterized in that: In step S3, the antioxidant is an ester, and the addition amount thereof is 0.5‰~1‰ of the weight of the samarium-cobalt dual alloy coarse powder; the lubricant is an alkane, and the addition amount thereof is 0.1‰~1.5‰ of the weight of the fine powder.

5. The high remanence samarium cobalt permanent magnet material according to claim 1, characterized in that: In step S4, the orientation magnetic field is 1.8-2.2 T, and the molding pressure is 3-5 MPa.

6. The high remanence samarium cobalt permanent magnet material according to claim 1, characterized in that: In step S5, the cold isostatic pressing pressure is 180-220 MPa, and the holding time is 10-30 s.

7. The high remanence samarium cobalt permanent magnet material according to claim 1, characterized in that: In step S7, the cooling rate of the first cooling is 0.15-0.8°C / min, and the cooling method of the second cooling is argon gas air cooling.

8. A high remanence samarium cobalt permanent magnet material according to any one of claims 1 to 7, characterized in that: The high remanence samarium cobalt permanent magnet material has a remanence greater than 11.8 kGs and a coercive force greater than 25 kOe.

Citation Information

Patent Citations

  • Method for producing samarium-cobalt series sintered materials

    CN102650004A

  • High-performance samarium cobalt permanent magnet

    CN108335813A